Delayed Facial Nerve Palsy Following Resection of Vestibular Schwannoma: Clinical and Surgical Characteristics. Issue 2 (25th February 2022) - MacDonald, Bridget V.; Ren, Yin; Shahrvini, Bita; Tawfik, Kareem O.; Moshtaghi, Omid; Schwartz, Marc S.; Friedman, Rick A.
Abstract : Objective: Analyze delayed facial nerve palsy (DFNP) following resection of vestibular schwannoma (VS) to describe distinct characteristics and facial nerve (FN) functional course. Study Design: Prospective cohort with retrospective review. Setting: Academic medical center. Patients: Consecutive patients undergoing VS resection 11/2017 to 08/2020. Exclusion criteria: preoperative House-Brackmann (HB) ≥ III, postoperative HB ≥ III without delayed palsy, <30 days follow-up. Interventions: VS resection with intraoperative electromyographic monitoring. Main Outcome Measures: FN outcomes utilizing the HB scale; comparison between patients with DFNP (deterioration greater than one HB grade 24 hours to 30 days postoperatively) vs. those with HBI–II throughout. Results: Two hundred eighty-eight patients met criteria: mean age 47.6 years, 36.1% male; 24.0% middle cranial fossa, 28.5% retrosigmoid, 47.6% translabyrinthine. DFNP occurred in 31 (10.8%) patients with average time to onset of 8.1 days. Of these, 22 (71.0%) recovered HBI–II and 3 (9.7%) recovered HBIII. Patients who experienced DFNP, on average, had larger maximum tumor diameter (23.4 vs. 18.7 mm, p = 0.014 ), lower rate of gross-total resection (54.8% vs. 75.5%, p = 0.014 ), and lower rate of ≥100 μV FN response to 0.05 mA stimulus intraoperatively (80.6% vs. 94.9%, p = 0.002 ). Compared to overall incidence of DFNP, translabyrinthine approach demonstrated higher incidence (15.3%, p = 0.017 ) while retrosigmoid lower (3.7%, p = 0.014 ). In multivariable logistic regression, patients with FN response ≥100 μV to 0.05 mA stimulus were 72.0% less likely to develop DFNP ( p = 0.021 ). Conclusions: Intraoperative electromyographic facial nerve response, tumor size, surgical approach, and extent of resection may play a role in development of DFNP following resection of VS. Most patients who develop DFNP recover near-normal function.